An Ontology for Supporting Digital Forensics Controlled Experiments: Early Stages of Development - Silva, Thiago J.; OliveiraJr, Edson (Anais do Brazilian e-Science Workshop (BreSci); 2022: Anais do XVI Brazilian e-Science WorkshopDO - 10.5753/bresci.2022.222813, 2022)
The experimentation process is one of the main means of science to evaluate theories based on hypothesis. Science evolves most taking into account the performing of controlled experiments, thus providing trust evidence for different research fields. However, for the Digital Forensics (DF) field, formal controlled experimentation has been neglected over the years. In a recent systematic mapping of the literature, we found more than 200 experiments with few formalization of their procedures, thus jeopardizing its evidence reliability and the capacity of reproducibility. Therefore, this paper provides early steps to specify an ontology for supporting proper planning, conducting, and dissemination of DF controlled experiments. The ontology has as a basis a conceptual model created to specify the main elements of an experiment. We adopted the Uschold and King approach to develop such an ontology. We first designed the ontology with the protégé ontology editor, as it organizes knowledge. In addition, the WebVOWL tool was also used from the json file generated in the protegé tool, as this aids at the construction of a dynamic visual identity for the ontology. As general results, we understand that despite the number of ontologies in the literature being relevant, few present a structure that satisfies a relation of similar objects for their properties, in addition do not covering the context of a DF experiment. Therefore, despite the ontology construction is in its early stages, it is expected that it will shad light to the field of experimentation in DF throughout a hierarchy and formalized process.